Arginine methylation facilitates the nuclear export of hnRNP proteins - Shen, Elisa C. (Cold Spring Harbor Laboratory Press, 1998)
Eukaryotic mRNA processing and export is mediated by various heterogeneous nuclear ribonucleoproteins (hnRNPs). Many of these hnRNPs are methylated on arginine residues. In the yeast, Saccharomyces cerevisiae, the predominant enzyme responsible for arginine methylation is Hmt1p. Hmt1p methylates both Npl3p and Hrp1p, which are shuttling hnRNPs involved in mRNA processing and export. Here, we employ an in vivo nuclear export assay to show that arginine methylation is important for the nuclear export of these hnRNPs. Both Npl3p and Hrp1p fail to exit the nucleus in cells lacking Hmt1p, and overexpression of Hmt1p enhances Npl3p export. The export of a novel hnRNP-like protein, Hrb1p, which does not bind poly(A)(+) RNA, however, is not affected by the lack of methylation. Furthermore, we find a genetic relationship between Hmt1p and cap-binding protein 80 (CBP80). Together, these findings establish that one biological role for arginine methylation is in facilitating the export of certain hnRNPs out of the nucleus.